PERANCANGAN SISTEM INFORMASI AKADEMIK BERBASIS WEB PADA RA TK AL-MUTTAQIN - Andi Iken Alifia Brilianti, - (2021)
In this modern era using technology is increasingly being implemented as a data collection process in various fields, one of which is field of school. In this research, author discuss about academic system on RA TK Al-Muttaqin is still manual and do not have a website-based information system. In the system that is currently running in the process of registering new students and delivering information, they still have to come to school and use paper media, while the data collection and reporting process in the ongoing system is still not systemized which currently uses Microsoft Office as a tool to manage data, but the most likely risk is data loss or damage. So that in this study the author will design a website-based academic information system that aims to facilitate the RA TK Al-Muttaqin in delivering information and the registration process, assessment and reporting and make it easier for parents to access information. The analysis method in system requirements uses PIECES then the design system applies the Waterfall method in which the model design process moves with concepts, namely design, implementation, testing, installation, problem solving, and maintenance. The method in design modeling in system design uses UML. The programming language applied in building the system uses PHP using the MySQL database management system and in running the server assisted by the XAMPP application. The results obtained from this study are the establishment of a system that can simplify the registration process, manage data and deliver information and report data.